Estrogen Protects against Oxidative Multiorgan Damage in Rats with Chronic Renal Failure - YEGEN, BERRAK; ŞENER, GÖKSEL; YÜKSEL, MERAL; KASIMAY ÇAKIR, ÖZGÜR; ÇETİNEL, ŞULE (TAYLOR & FRANCIS LTD, 2009)
The impact of sex dimorphism on chronic renal failure (CRF)-induced oxidative multiorgan damage and the effects of estradiol (E-2) loss and E-2 supplementation on the progress of CRF were studied. Sprague-Dawley rats underwent 5/6 nephrectomy (CRF), and a group of female rats had bilateral ovariectomy (OVX), while the sham-operated rats had no nephrectomy or OVX. Rats received either estradiol propionate (50 mu g/kg/day) or vehicle for six weeks. Serum BUN levels were elevated in both male and female CRF groups treated with vehicle, while creatinine level was not significantly changed in the female CRF group. CRF-induced elevation in serum TNF-alpha of male rats was abolished when the animals were treated with E-2, while OVX exaggerated TNF-alpha response. In OVX and male rats with CRF, E-2 treatment reversed the malondialdehyde elevations in all the studied tissues (kidney, heart, lung, ileum, brain, liver, and gastrocnemius muscle), while depletion of glutathione in these tissues was prevented by E-2 treatment. Similarly, increased levels of myeloperoxidase activity, lucigenin chemiluminescence, and collagen in most of the tissues were reversed by E-2 treatment. The findings show that the extent of tissue injuries was relatively less in females, while ovariectomy exacerbated all the indices of oxidative injury. Moreover, the administration of E-2, with its potent anti-oxidant and anti-inflammatory effects, markedly improved CRF-induced systemic inflammatory outcomes in both male and female rats by depressing tissue neutrophil infiltration and modulating the release of inflammatory cytokines.
Keywords: estradiol; chronic renal failure; TNF-alpha; myeloperoxidase; lipid peroxidation; ISCHEMIA-REPERFUSION INJURY; NITRIC-OXIDE SYNTHASE; 17-BETA-ESTRADIOL SUPPLEMENTATION; HEMODIALYSIS-PATIENTS; ANTIOXIDANT SYSTEM; SEXUAL-DIMORPHISM; BLOOD-PRESSURE; IN-VITRO; STRESS; DISEASE